RESEARCH OF PROCESS THRESHING KOLOSOV WOROCH - Poustovit S. V.; Katkov V. I. (Вісник Уманського національного університету садівництва, 2016)
Article dedicated to the a comprehensive study of the process threshing of kolosov woroch. Together with the study of components woroch the output into the camera kolosov auger combine harvester submitted to rethreshing, determined the indicators of quality of of work purification and conveying of threshing device. The work scientifically justifiable and proved that with increase downloads purification from 1,0 to 6,0 kg/s, reducing the separation the coefficient of is observed. Install sieve before the separate obmolochuvalnym the device can distinguish woroch of threshed grain and small impurities and particles neobmolochenyh ears of corn and big impurities are east to the second thrashing that will reduce injury grains. Checking the efficiency of establish separate of sieve showed that the yield of grain after neobmolochenoho obmolochuvalnoho device changes depending on the downloading purification from 1 to 3%. Based on the research developed experimental installation for research of doobmolotu kolosov woroch combine harvesters KZS-9-1 «Slavutich».